Addressing the knowledge gap of Indigenous public health: reflections from an Indigenous public health graduate. Issue 2 (9th December 2020) - Lee, Natasha
Abstract: The current agenda in public health training in higher education works to produce well-trained public health professionals. Operating within a western pedagogical framework it aims to build a cohort of critical and analytical thinkers, skilful problem solvers and extraordinary communicators across key disciplines in health. Many graduates possess interdisciplinary specialities, skills and knowledge transferable within health and other sectors. Core competencies in the curricula, which notably does not currently include Indigenous health, are considered the foundational platform of theory and practical understandings of public health and the health system. Despite a framework that aims to produce health professionals capable of improving the health of the population as a whole; the lack of engagement with an Indigenous health criticality maintains a longstanding Australian public health tradition of failure when it comes to addressing the health disparities experienced by Indigenous people. As a recent Indigenous public health graduate with practical training and experience working in the public health system, I consider possibilities for decolonising the curricula through an Indigenist approach to health, including theories of transformative learning which could strengthen public health practice and in turn facilitate the changes necessary to improving Indigenous health outcomes.